Learn how to make and use compost manure in farming - Ngeze, P.B. (CTA / Acacia Stantex Publishers / Friends-of-the-Book Foundation, 1998)
This book deals with the preparation of high-quality compost manure and its application. Covering topics such as soil, fertilisers, how to prepare compost manure and the benefits of its use, the title will help farmers improve both yields and productivity.